The Effect of Implementing Suscatin KUA Makassar City on the Readiness of Prospective Married Couples to Build a SAMAWA Family - Jumliadi (Jurnal Al-Qadau: Peradilan dan Hukum Keluarga Islam, 2024)
This research is a quantitative research with an experimental approach, pre-experimental method with a one group pretest-posttest design. The research was carried out by the Makassar City Office of Religious Affairs (KUA), with the subjects being 40 prospective married couples. The sampling technique in this research is simple random sampling. Data collection techniques are carried out through observation, questionnaires and documentation. The data was then analyzed using descriptive and inferential analysis using SPSS. The results of the descriptive analysis where the average pre-test score was 48.24 and the average post-test score was 86.00 in the very good category, then the results of the inferential analysis where the normality test was 0.300, the homogeneity test was 0.633 and the t-test result was 0.000, from these results It was concluded that there was an influence of the implementation of Suscatin KUA Makassar City on the readiness of prospective married couples to build a SAMAWA family.